The Formation and Development of Foreign Sociology of Higher Education: A Review - G. E. Zborovsky; P. A. Ambarova (Moscow Polytechnic University, 2020)
The review article summarizes the processes of development of higher education sociology abroad over the past 50 years. The choice of the research object was determined by the real achievements of national higher education systems and a high level of higher school sociology development in USA, Great Britain, France, Scandinavian countries, and Spain. The review reflects the advancement of leading sociologists of higher education in these countries. The authors have applied a methodology of comparative analysis studying the Western experience of sociological research in higher education, the main ideas and trends. The article dwells on the ways of changes in the content field of Western sociology of higher education. The practical significance of the review is determined by the possibilities of using the proposed analysis for the development of Russian sociology of higher education and University development practices.